The Red Sea conflict and market reactions: Examining the role of military strength in financial markets - Rizky Yudaruddin; Dadang Lesmana; İbrahim Halil Ekşi; William Ginn; Mosab I. Tabash (Peace Economics, Peace Science and Public Policy (PEPS), 2025)
This study examines market reactions to the US-Houthi conflict on January 11, 2024, across various markets, regions, and industries within the financial sector, emphasizing the role of military strength in shaping global financial responses. An event study methodology is applied to a sample of 3,239 financial sector companies, observing market reactions over multiple event windows: a 15-day pre-event phase and a 15-day post-event phase surrounding the conflict announcement. Cross-sectional analysis is conducted to assess how military strength impacts financial market reactions. The results indicate significant market vulnerability to the US-Houthi conflict, particularly during the period from the event day on January 11, 2024, to the post-event phase, with developed markets experiencing the greatest impact. While American markets showed mixed responses, European, Middle Eastern, and African markets faced notable negative effects due to disrupted trade routes; Asian markets also showed negative reactions, though to a lesser extent. The banking industry recorded the most adverse reaction within the financial sector, and military strength emerged as a critical factor influencing investor behavior in response to the conflict. These findings highlight the need for policymakers to enhance financial market stability by considering military strength and trade route security in risk mitigation strategies, particularly in times of geopolitical uncertainty, such as the period surrounding the US-Houthi conflict in early 2024.
Keywords: G39; G41; F51; D53; E44; 320; event study; financial sector; market reaction; military strength; US-Houthi conflict